Calcium-independent membrane damage by venom phospholipases A2 - De Oliveira, A. H.C.; Aragão, E. A.; Sá, J. M.; Chioato, L.; Bugs-Bortoleto, R. [UNESP]; Ruller, R.; Ferreira, T. L.; Ward, R. J. (Bentham Science Publishers, 2009)
Many snake venom phospholipase A2s (vPLA2s) present biological effects that are independent of hydrolytic activity. Here we review the evidence for the calcium-independent membrane damaging activity of vPLA 2s, the possible relevance of this activity on their biological effects, and models for the mechanism of membrane permeabilization by these proteins. © 2009 Bentham Science Publishers Ltd.
Keywords: Membrane permeabilization; Micelle nucleation; Molecular mechanism